Nature of the interaction between ammonia derivatives and carbon disulfide. A theoretical investigation. Issue 11 (2nd March 2017) - Zierkiewicz, Wiktor; Michalczyk, Mariusz; Bieńko, Dariusz; Michalska, Danuta; Zeegers‐Huyskens, Thérèse
Abstract: The interactions between NH3, its methylated and chlorinated derivatives and CS2 are investigated by ab initio CCSD(T) and density functional BLYP‐D3 methods. The CCSD(T)/aug‐cc‐pVTZ calculated interaction energies of complexes characterized by the S···N chalcogen bonds range between −1.71 and −2.78 kcal mol −1 . The S···N bonds are studied by atoms in molecules, natural bond orbital, and noncovalent interaction methods. The lack of correlation between the interaction energies of methylated amines complexes and the electrostatic potential results from the lone pair effect in aliphatic amines. Different structures of CS2 complexed with ammonia derivatives, stabilized by other than the S···N chalcogen bonds, are also predicted. These structures are characterized by interaction energies ranging between 1.15 and 3.46 kcal mol −1 . The results show that the complexing ability of CS2 is not very high but this molecule is able to attack the electrophilic or nucleophilic sites of a guest molecule. Abstract : The S···N interaction (a noncovalent chalcogen bond) has attracted much attention owing to its significance in the biological activity of some sulfur containing compounds, as, for example, proteins with cysteine and methionine amino acid residues. In this work, model compounds composed by the CS2 complexes with ammonia and its chlorinated and methylated derivatives are studied by means of first‐principles calculations.